Dalsza cześć wyrażeń algebraicznych
26.0,1(4a-5b)-0,2(3a+4b) =
27. 7/12(1/7a+4/21b)+9/10(⅓a-5/6b) =
29.1,1(1,1a-1,2b)+1,2(1,2a+1,1b) =
30. 2,5x²-[0,6x²-(3,5x+x²)-(x²+3x)]+[0,1x²-(x²-3,5x)+x²] =
31. x-1,4xy+1,2y-[1,6xy-{0,6y-(1,4x-4,4xy)]-(1,4xy-16y)} =
32. 2,6x-{1,8y-[2,2x-(j-0,6x)+1,4j]-[1,6x-0,2x]} =
33. 3x×[5y-(7x-4j)]-8j+[3x-(7y-5x)+6x-11j)] =
34. x²[4,8x²-0,6j(1,6x-1,4j)]-1,2y²×[3,6x²-1,6x(0,8x-1,4y)+2,4y²] =
35. 1⅓x×[4½x-(3¾j-31½)]-[12⅓x-(11 3/7-8⅓j0]×4⅕j =
36. 0,3a-(1,4b-0.8c)+(-a+0,6b-0,2c)-(-0,7a-0,8b) =
37. 0,5(2x-y)+¾(x+2x)+1,75x+y) =
38.3a²-[4a2-3b²+[(4b²-8a²)-(5a²-5b²)+(-3a²+4b²)]+8a²-5b²}+5b² =

1

Odpowiedzi

2010-02-17T17:54:47+01:00
26.0,1(4a-5b)-0,2(3a+4b) = 0,4a - 0,5b - 0,6a - 0,8b = -0,2a - 1,3b
29.1,1(1,1a-1,2b)+1,2(1,2a+1,1b) = 1,21a - 1,32b + 1,44a + 1,32b = 2,64a